Pengaruh Religiusitas, Pemahaman, Kepercayaan dan Lingkungan Sosial Terhadap Minat Membayar Zakat Tijarah Pedagang Pasar Tradisional Palembang - Elsa Julia; Peny Cahaya Azwari; Bunga Mar’atush Shalihah (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2024)
This research aims to determine the influence of Religiosity, Understanding, Trust and Social Environment on the Interest in Paying Zakat Tijarah of Traditional Market Traders in Palembang City. This population is 100 traditional market traders. The sampling technique uses incidental sampling, namely a sampling technique whose determination is based on chance, that is, anyone who coincidentally (incidentally) meets the researcher will be used as a sample. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3 software. PLS is a method for solving Structural Equation Modeling (SEM) which in this case is more compared to other SEM techniques, which consist of convergent validity tests, Avarage Variance Extracted, Reability Test, Cronbach Alpha, Discriminant Validity Test, Structural Model Test, and Hypothesis Test From the results of the hypothesis test, the religiosity variable has no influence on traders' interest in paying zakat. The understanding variable has a positive effect on muzakki interest. Test the hypothesis that the trust variable has no effect on traders' interest in paying zakat. The results of the hypothesis test of social environmental variables have no effect on traders' interest in paying zakat.